Leading with Intelligence : How AI is Reshaping Creative Innovation in Organizations - Kumar, Anuj; Banerjee, Padmakali (Prabandhan: Indian Journal of Management, 2025)
Purpose : The objective of the paper was to synthesize primary research related to the impact of artificial intelligence (AI) on creative innovation in organizations. As companies in different sectors digitally transform, AI has the potential to improve efficiency, along with being a catalyst for creative innovation, from product ideas and design to challenge mitigation and business model evolution. By an extensive review of literature, this paper presented how AI-driven platforms, tools, and processes challenge traditional processes, foster creativity, and reshape innovation. Methods : The study is a systematic review of 14 peer-reviewed articles from 2020 to 2025. Scopus and Google Scholar were used for searching the relevant articles on contemporary trends in AI-driven innovation. Significant Findings : AI enables significant changes to knowledge work, the ideation process, and creative workflow by augmenting human talent, not just automating tasks. Organizational structures were inclining toward digital integration, agility, and cross-functionality; however, creative confidence is driven by AI. Research revealed that AI enhances both incremental and disruptive innovation, and to realize these advantages, continuous talent development and responsible governance are required. Novelty : Unlike other reviews, this paper exclusively focused on recent articles to provide a comprehensive, cross-sectoral, and current view. Its novelty is in the multilevel framework that connects technological, managerial, and cognitive aspects in AI-supported creative practice. Implications : For policymakers and practitioners, leveraging AI’s creative potential requires continuous upskilling, investment in digital infrastructure, and ethical governance. Researchers should explore innovation parity, longitudinal creative impact, and social dynamics in future research.